Use of dye complexation dynamics to determine α‐cyclodextrin host:guest stability constants. (12th February 2018) - Rodríguez, María; Silva, Lara; Parajó, Mercedes; Rodríguez‐Dafonte, Pedro; García‐Río, Luis
Abstract: Dynamics of host:dye complexation have been used, as an alternative to displacement assays, for determination of additional host:guest stability constants. Requirement of this new methodology is host:guest complexation being much faster than host:dye in order to guaranty that host:guest system is in equilibrium at each time during dye inclusion into the host cavity. Methodology was tested by studying α‐CD:surfactant complexation using alkyltrimethylammonium surfactants with different alkyl chain length. Experimental results confirm the formation of 1:1 α‐CD:surfactant complexes with binding constants strongly dependent on the surfactant hydrophobicity. Abstract : Dynamics for ethyl orange inclusion into the cyclodextrin cavity are strongly affected by the concentration of uncomplexed host. Equilibrium constants for very fast inclusion process can be obtained from ethyl orange inclusion kinetics.